Machasories Product Development as an Aesthetic Accessory Business to Improve Digital Business Literacy Capabilities in Generation Z - Annisa Bella Haryanti; Ayuni Nisa Syafira; Ade Tya Eka Putri; Meicella Rizky Arincia (CV. Media Inti Teknologi, 2023)
This research is research into the development of machasories products, namely as a contemporary, aesthetic accessory business which of course is currently very popular among teenagers and all groups. This research uses descriptive and quantitative analysis techniques. In this research, we used data collection techniques through questionnaires that we gave to customers who had already ordered accessory products, we got 86.6 quality and preferred accessories in terms of beauty and aesthetics. Of course, there are shortcomings that we found in the questionnaire that we have distributed, namely that there are products that are not neat in workmanship and the manufacturing process takes a long time. In this research, the aim is that the development of accessories business products can increase digital business literacy in generation Z, of course this will be an important thing in the future as a reference for generation Z to start a business to produce work and earn income.